Rapid Response to Effusive Eruptions Using Satellite Infrared Data: The March 2024 Eruption of Fernandina (Galápagos) - Diego Coppola; Simone Aveni; Adele Campus; Marco Laiolo; Francesco Massimetti; Benjamin Bernard (Remote Sensing)
On 3 March 2024, a new effusive eruption began from a sub-circular fissure on the southeast upper flank of the Fernandina volcano (Galápagos archipelago, Ecuador). Although the eruption posed no threat to people, as the island is uninhabited, it provided an opportunity to test a rapid response system for effusive eruptions, based on satellite infrared (IR) data. In this work, we illustrate how the analysis of data from multiple IR sensors allowed us to monitor the eruption in near real-time (NRT), providing recurrent updates on key parameters, such as (i) lava discharge rate and trend, (ii) erupted lava volume, (iii) lava field area, (iv) active flow front position (v) flow velocity, (vi) location of active vents and breakouts, and (vii) emplacement style. Overall, the eruption lasted 68 days, during which 58.5 ± 29.2 Mm3 of lava was erupted and an area of 14.9 ± 0.5 km2 was invaded. The eruption was characterized by a peak effusion rate of 206 ± 103 m3/s, an initial velocity of ~2.3 km/h, and by an almost exponential decline in the effusion rate, accompanied by a transition from channel- to tube-fed emplacement style. The advance of the lava flow was characterized by three lengthening phases that allowed the front to reach the coast (~12.5 km from the vent) after 36 days (at an average velocity of ~0.015 km/h). The results demonstrate the efficiency of satellite thermal data in responding to effusive eruptions and maintaining situational awareness at remote volcanoes where ground-based data are limited or completely unavailable. The requirements, limitations, and future perspectives for applying this rapid response protocol on a global scale are finally discussed.